Understanding the Relation of Maqasid al-Shari’ah and Islamic Economic Development to Develop a Better Islamic Entrepreneurial Culture in Schools - Zeti Nur Aimar binti Alli; Rossidi bin Usop (Kolej Genius Insan, Universiti Sains Islam Malaysia, 2024)
2nd Insan Junior Researchers International Conference 2021 (iJURECON 2021) “STREAM for a Better Life” 15-17th October 2021 Organized By :Kolej GENIUS Insan of Universiti Sains Islam Malaysia